Security user authentication procedures of web-applications - Коломыцев, Михаил Владимирович; Носок, Светлана Александровна; Грайворонский, Николай Владленович (Ukrainian Information Security Research Journal, 2014)
Nowadays interactive Web-applications are an essentialpart of the information systems of business, governmentalstructures, etc. The main feature of such systems is toorganize the client access, business partners and employeesto the resources of the Internet. For access to onlineservices and defining the level of authority, users mustclearly identify themselves. There are many ways to organizethe process of users authentication; the mostcommon way is authentication with the help of forms. Inthis article the questions connected with increasing securityof the authentication process and control user sessionsare considered.